2012
DOI: 10.1039/c2cc17795a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cellulose–chitosan hydrogels prepared from ionic liquids as reusable adsorbent for removal of heavy metal ions

Abstract: Magnetic hybrid hydrogels with a novel polymeric coating consisting of chitosan and cellulose were prepared. By coating cellulose and chitosan, we combined the renewability and biocompatibility of cellulose and chitosan as well as the magnetic properties of Fe(3)O(4) to create a hybrid system to adsorb heavy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(121 citation statements)
references
References 34 publications
3
116
0
2
Order By: Relevance
“…It is worthy to note that cellulose may be acted as a promising surface material, because of its abundance of hydroxyl groups. These hydroxyl groups may promote the adsorption of metal ions for the formation of MOF crystal (Liu et al 2012). Cellulose is the most abundant renewable polysaccharide on earth, which is sustainable, biocompatible, biodegradable, and non-toxic (Lavoine et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that cellulose may be acted as a promising surface material, because of its abundance of hydroxyl groups. These hydroxyl groups may promote the adsorption of metal ions for the formation of MOF crystal (Liu et al 2012). Cellulose is the most abundant renewable polysaccharide on earth, which is sustainable, biocompatible, biodegradable, and non-toxic (Lavoine et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the Pb(II) sorption capacities of our OCB sorbents compare very favorably to those values (Table S2, Supporting Information) reported for Zn 2 GeO 4 -ethylenediamine hybrid nanoribbons (74.6 mg g −1 ), [ 2 ] sulfonated polyphenyldiamine (91.8 mg g −1 ), [ 16 ] longan shell (52.1 mg g −1 ), [ 17 ] polyvinylbutyral microbeads (86.2 mg g −1 ), [ 18 ] polysulfoaminoanthraquinone nanoparticles (89.6 mg g −1 ), [ 19 ] diethylenetriamine-bacterial cellulose (22 mg g −1 ), [ 20 ] meranti sawdust (34.3 mg g −1 ), [ 21 ] thiol-functionalized ceramic hybrids (22.4 mg g −1 ), [ 22 ] activated carbon (4.77 mg g −1 ), [ 23 ] titanosilicate ETS-10 (56.3 mg g −1 ), [ 24 ] and cellulose-chitosan hydrogels (28.1 mg g −1 ). [ 25 ] More importantly, the production of OCB microspheres is a low-cost and environmentally friendly process owing to the cheap starting materials and simple one-step aqueous synthesis. This stands in contrast to most synthetic macrocycles that are expensive to prepare and likely to cause secondary pollution since the multistep syntheses are largely conducted in organic solvent systems and noble metal catalysts are often required.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 illustrates the overall process of adsorption, desorption and recycling in using magnetite cellulosechitosan hydrogels for the removal of metal ions [52]. These studies have shown that the hydrogels had scarce affinity to Mn(II), Zn(II), and Ni(II), but exhibited high affinity to Cu(II), Fe(II), and Pb(II), with corresponding equilibrium adsorption capacities (mg/g) of, respectively, 44.7 ± 5, 94.1 ± 7 and 28.1 ± 3 of the adsorbent (dried weight).…”
Section: Removal Of Metal Ionsmentioning
confidence: 99%
“…One-step coating of Fe 3 O 4 nanoparticles with cellulose and chitosan was performed using ionic liquids as solvents [52]. Cellulose was used here as a blending agent for chitosan, leading to materials (average size 200 μm) with superior mechanical strength as well as to improve chemical stability in acidic medium.…”
Section: Magnetic Bionanocompositesmentioning
confidence: 99%